Nano-zeolite-modified concrete: A comprehensive study of mechanical properties, corrosion resistance, and microstructural of concrete under varied exposure conditions - Ahmed Elsayed Mohamed; Magdy Ali Abdelaziz; Ahmed Serag Farid; Khaled M. Osman (Cleaner Engineering and Technology)
This study investigates the application of natural milling Nano Zeolite (NZ) on concrete, a crystalline aluminosilicate mineral with distinctive microporous structures, and the promotion of eco-friendly building endeavors. The research examined the impact of NZ on the behavior of concrete exposed to internal and external chloride and sulphate attacks. NZ was used as a substitute for cement at various weight percentages. Compressive, flexural, indirect tensile strength, SEM, and EDX tests were performed. Potentiodynamic polarization was used to determine corrosion rates. The results demonstrated that the incorporation of NZ enhanced the mechanical and microstructural properties of concrete. The optimal percentage of nano zeolite was 3% at normal conditions. In internal attack conditions, 1.5% NZ was the optimal percentage due to its significant aluminum content, which enhances the formation of ettringite. The optimal percentage for external attack was 4.5% NZ, as NZ acts as a filler agent at early ages due to delayed hydration. Moreover, NZ significantly improved the concrete matrix, resulting in a denser microstructure. The corrosion resistance of concrete samples exposed to normal and internal attack circumstances exhibited the optimum efficiency of 3% NZ, while 4.5% NZ was optimal for concrete samples exposed to external attack.